Contesting Ideologies of Natural Resource Development in British Columbia, Canada - S. Trigger, David (Culture, 1996)
The ideological struggle between pro-development sentiments and environmentalist challenges to them is a complex mix of consciously articulated beliefs and commonsense assumptions about what land isfor and how it should be managed. The paper presents an ethnographic approach to documenting expressions of this intellectual contest in contemporary British Columbia. I address the question of how pro-development and pro-wilderness views seek to establish moral authority, focusing on both the symbolic importance of key themes about forestry and mining in Canadian history and the cooption of alleged aboriginal ethics concerning land use.